The Study Of Anticancer Properties Of Benzyl-O-Vanillin And Its Derivatives - Al-Mudaris, Zena A. Abdul Hameed (2011)
Benzyl-o-vanillin and benzimidazole nucleus serve as important pharmacophore in drug discovery as it has a significant medicinal importance. Thus we explored the anticancer activity of three compounds namely 2-(2-benzyloxy-3-methoxyphenyl)-1H-benzimidazole, 2MP, N-1-(2-benzyloxy-3-methoxybenzyl)-2-(2-benzyloxy-3-methoxyphenyl)-1H-benzimidazole, 2XP, and (R) and (S)-1-(2-benzyloxy-3-methoxyphenyl)-2, 2, 2-trichloroethyl benzenesulfonate, 3BS and compared their activity to 2-benzyloxy-3-methoxybenzaldehyde, (Bn1) the parent compound. 2XP and 3BS were found to be selectively cytotoxic towards U937 leukemic cell causing cell death via apoptosis by activating caspase 9 activity.